An Atypical Acyl‐CoA Synthetase Enables Efficient Biosynthesis of Extender Units for Engineering a Polyketide Carbon Scaffold. (30th September 2022) - Zheng, Mengmeng; Zhang, Jun; Zhang, Wan; Yang, Lu; Yan, Xiaoli; Tian, Wenya; Liu, Zhihao; Lin, Zhi; Deng, Zixin; Qu, Xudong
Abstract: Acyl‐CoAs are key precursors of primary and secondary metabolism. Their efficient biosynthesis is often impeded by the limited substrate specificity and low in vivo activity of acyl‐CoA synthetases (ACSs) due to regulatory acylation of the catalytically important lysine residue in motif A10 (Lys‐A10). In this study, we identified an unusual ACS (UkaQ) from the UK‐2A biosynthetic pathway that naturally lacks the Lys‐A10 residue and exhibits extraordinarily broad substrate specificity. Protein engineering significantly improved its stability and catalytic activity, enabling it to synthesize a large variety of acyl‐CoAs with highly robust activity. By combining it with permissive carboxylases, we produced a large array of polyketide extender units and obtained six novel halobenzyl‐containing antimycin analogues through an engineered biosynthetic pathway. This study significantly expands the catalytic mode of ACSs and provides a potent tool for the biosynthesis of acyl‐CoA‐derived natural products. Abstract : A new acyl‐CoA synthetase (ACS, UkaQ) with broad substrate specificity and an unusual catalytic mode was identified. Its stability and catalytic activity were remarkably improved by protein engineering, enabling it to synthesize a large variety of acyl‐CoAs. In combination with permissive carboxylases, diverse extender units were synthesized and used to engineer the polyketide carbon scaffold of antimycin.